Evaluation of the Biogenic Amines and Microbial Contribution in Traditional Chinese Sausages - Li, Lu; Zou, Dian; Ruan, Liying; Wen, Zhiyou; Chen, Shouwen; Xu, Lin; Wei, Xuetuan (Frontiers in Microbiology, 2019)
Biogenic amines (BAs) in sausages represent a health risk for consumers, and thus investigating the BAs accumulation mechanism is important to control the BAs. In this study, the BAs profiles of 16 typical Chinese sausage samples were evaluated, and 8 kinds of common BAs were detected from different samples. As a whole, the BAs contents of the majority of Chinese sausage samples were within the safe dosage range, except that the total BAs and histamine concentrations of sample HBBD were above the toxic dosage levels. Furthermore, the bacterial and fungal communities of the Chinese sausage samples were investigated by high-throughput sequencing analysis, and Staphylococcus, Bacillus, Lactococcus, Lactobacillus, Debaryomyces and Aspergillus were identified as the predominant genera. Accordingly, thirteen representative strains were selected from the dominant genera, and their BAs formation and degradation properties were evaluated. Finally, the results of fermented meats model experiment indicated that the Staphylococcus isolates including S. pasteuri Sp, S. epidermidis Se, S. carnosus Sc1, S. carnosus Sc2 and S. simulans Ss could significantly reduce BAs, possessing the potential as the starter cultures to control the BAs in fermented meat products. The present study not only helped to explain the BAs accumulation mechanism in Chinese sausage, but also developed the candidates for potential BAs control in fermented meat products.